Analisa Proses Seleksi Pendanaan Renovasi Mesjid dengan SAW - Cici Rezky; Rizky Fauziah; Tika Christy (J-Com (Journal of Computer), 2022)
Abstrack: Mosque renovation is one of the service activities provided by the government to residents who submit applications. The Ministry of Religion of Tanjungbalai City is one of the governments that provides services related to religion, especially in requests for assistance for mosque renovations. The decision-making process in determining mosque renovation assistance at the Ministry of Religion of Tanjungbalai City is still done manually. The purpose of this research is to help provide solutions in the process of determining mosque renovation assistance to be faster because the process of utilizing information technology as a tool to help run the government system more effectively and efficiently. The SAW method is more efficient because the time required for calculations is faster. From the results of making a decision support system for determining mosque renovation assistance, it can improve and assist the performance of the Ministry of Religion of Tanjungbalai City, so that the performance of the agency and the decision-making process becomes faster, more accurate and efficient. Keywords: Simple Additive Weighting; Decision Support System; Mosque Renovation  Abstrak: Renovasi mesjid merupakan salah satu kegiatan pelayanan yang diberikan pemerintah kepada warga yang mengajukan permohonan. Kementerian Agama Kota Tanjungbalai merupakan salah satu pemerintahan yang menyediakan pelayanan seputar keagamaan terkhusus dalam permohonan bantuan renovasi mesjid. Proses pengambilan keputusan dalam penentuan bantuan renovasi mesjid di Kementerian Agama Kota Tanjungbalai masih dilakukan secara manual. Adapun tujuan penelitian ini adalah untuk membantu memberikan solusi dalam proses penentuan bantuan renovasi mesjid menjadi lebih cepat karena proses pemanfaatan teknologi informasi sebagai alat untuk membantu menjalankan sistem pemerintahan secara lebih efektif dan efesien. Metode SAW ini lebih efisien karena waktu yang dibutuhkan dalam perhitungan lebih cepat. Dari hasil pembuatan sistem pendukung keputusan penentuan bantuan renovasi mesjid dapat meningkatkan dan membantu kinerja di Kementerian Agama Kota Tanjungbalai, sehingga kinerja instansi dan proses pengambilan keputusan tersebut menjadi lebih cepat, akurat dan efesien. Kata Kunci: Simple Additive Weighting; Sistem Pendukung Keputusan; Renovasi Mesjid